Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
https://doi.org/10.13016/M2QR4NT6S
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

La lesbienne fin-de-siècle : une fiction portugaise - Curopos, Fernando (Moderna Sprak, 2018)
La figure de la lesbienne a hanté la littérature érotique et pornographique bien avant que l'homosexualité ne soit « inventée » (Foucault) par la médecine psychiatrique dans le troisième quart du XIXe siècle. Cet article traite de la représentation de la « lesbienne » dans la littérature portugaise. littérature de siècle. Ces lesbiennes, créées par et destinées à un public masculin, sont le résultat et le produit d'un « esprit droit » (Wittig) qui fantasme les relations entre femmes tout en effaçant la réalité : la possibilité d'un véritable amour entre femmes. Néanmoins, au tournant du siècle, certaines d'entre elles sortiront du placard, plus ou moins forcées, donnant un « visage » à la lesbienne portugaise invisible
https://www.researchgate.net/publication/331274821_La_lesbienne_fin-de-siecle_une_fiction_portugaise
Keywords: approches et analyses; arts; discipline; discours dominant; europe; hétérosexisme; lesbianisme; personnes lesbiennes; portugal; ressource en ligne; régions géographiques; systèmes d'oppressions; études littéraires

Inconsequence: Lesbian representation and the logic of sexual sequence - Jagose, Annamarie (Cornell University Press, 2018)
The field of lesbian studies is often framed in terms of the relation between lesbianism and invisibility. Annamarie Jagose here takes a radical new approach, suggesting that the focus on invisibility and visibility is perhaps not the most productive way of looking at lesbian representability. Jagose argues that the theoretical preoccupation with metaphors of visibility is part of the problem it attempts to remedy. In her account, the regulatory difference between heterosexuality and homosexuality relies less on codes of visual recognition than on a cultural adherence to the force of first order, second order sexual sequence. As Jagose points out, sequence does not simply specify what comes before and what comes after; it also implies precedence: what comes first and what comes second. Jagose reads canonical novels by Charles Dickens, Henry James, Virginia Woolf, and Daphne du Maurier, drawing upon their elaboration of sexual sequence. In these innovative readings, tropes such as first and second, origin and outcome, and heterosexuality and homosexuality are shown to reinforce heterosexual precedence. Inconsequence intervenes in current debates in lesbian historiography, taking as its pivotal moment the fin-de-siècle phenomenon of the sexological codification of sexual taxonomies and concluding with a reading of a post-Kinsey pulp sexological text. Throughout, Jagose reminds us that categories of sexual registration are always back-formations, secondary, and belated, not only for those who identify as lesbian but also for all sexual subjects.
Keywords: approches et analyses; arts; discipline; discours dominant; littérature; personnes lesbiennes; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

Libère-toi Cyborg! : le pouvoir transformateur de la science-fiction féministe - Larue, Ïan (Éditions Cambourakis, 2018)
Gynoïdes, sorcières, vampires, chiennes et souris de laboratoire : toutes sont liées à la cyborg de Donna Haraway. Reprenant la liste d'auteurs et autrices de science-fiction féministe citées à la fin du Manifeste cyborg, Ïan Larue redéfinit cette figure fondatrice dans la pensée de la philosophe :"La cyborg, c'est l'esclave noire qui apprend à lire dans un roman d'Octavia Butler ; la jeune fille encapsulée qui, loin de se sentir handicapée, connaît des milliers de connexions ; la fille-orque transportée dans les étoiles. La cyborg est l'hybride suprême, hybride entre une femme réelle et un personnage de roman qui se superpose à elle pour la doter de mille nouvelles possibilités dont celle, fondamentale, de faire éclater capitalisme, famille et patriarcat."
Keywords: approches et analyses; arts; corps; cours; discipline; fem3600; patriarcat; premier cycle; systèmes d'oppressions; thématiques; écoféminisme; études littéraires

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne Betasamosake; Régimbald, Anne-Marie (Varia, 2018)
"On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale."– Renaud-Bray.
Section: 216 pages ; 21 cm.
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; militance; ojibwa; premier cycle; premières nations; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires